ANALISIS KELAYAKAN FINANSIAL USAHA PENGGILINGAN PADI KELILING DI KABUPATEN PRINGSEWU PROVINSI LAMPUNG - Riki Arya Dinata; Wan Abbas Zakaria; Teguh Endaryanto (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
The study aimed to analyze financial, sensitivity, and institutional aspect of mobile rice mill business. The research location was chosen purposively in Ambarawa Sub district of Pringsewu Regency, Lampung Province.  The study was conducted by census method on all three rice mill machine owners.  The investment of rice mill business was begun in 2010. The data was analyzed by financial feasibility and sensitivity analysis.  Qualitative descriptive analysis was also used to analyze the institutional aspect. The result showed that the business of mobile rice mill machine was financially feasible in which value of Net Present Value was Rp78,899,247.46.  The Internal Rate of Return value was 34.37 percent, greater than the interest rate used of 9.75 percent.  The Gross B/C value was 1.13 and the Net B/C value was 1.75.  The value of Payback Period was 3.18 years of the machine’s economic life for seven years. Rice mill business was still feasible despite decrease in income of 3.29 percent and an increase in operational cost of 3.53 percent.  The institutional system should be simplified with clear licensing and area of work. Key words: financial, institutional, mobile rice mill, sensitivityThe study aimed to analyze financial, sensitivity, and institutional aspect of mobile rice mill business. The research location was chosen purposively in Ambarawa Sub district of Pringsewu Regency, Lampung Province.  The study was conducted by census method on all three rice mill machine owners.  The investment of rice mill business was begun in 2010. The data was analyzed by financial feasibility and sensitivity analysis.  Qualitative descriptive analysis was also used to analyze the institutional aspect. The result showed that the business of mobile rice mill machine was financially feasible in which value of Net Present Valuewas Rp78,899,247.46.  The Internal Rate of Return value was 34.37 percent, greater than the interest rate used of 9.75 percent.  The Gross B/C value was 1.13 and the Net B/C value was 1.75.  The value of Payback Period was 3.18 years of the machine’s economic life for seven years. Rice mill business was still feasible despite decrease in income of 3.29 percent and an increase in operational cost of 3.53 percent.  The institutional system should be simplified with clear licensing and area of work. Key words: financial, institutional, mobile rice mill, sensitivity